IMPLEMENTATION OF SHARIA PRINCIPLES IN THE SETTLEMENT OF MURABAHAH FINANCING DEFAULT AT PT BPRS TAMAN INDAH DARUSSALAM - Riski, M. Romi; Badri, Khairul; Husnul, Muhammad (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2025)
Financing is a core activity in Islamic banking that plays a crucial role in supporting economic growth. In practice, some customers have defaulted on murabahah financing for motorcycle purchases at PT BPRS Taman Indah Darussalam from 2019 to 2021. These defaults took the form of continuous late payments and payment arrears, resulting in the temporary suspension of the repayment process. This study focuses on the concept and implementation of the murabahah agreement applied by PT BPRS Taman Indah Darussalam, the forms and causes of customer default, and its impact on bank stability. The method used is qualitative with a legal-empirical approach, through direct interviews and documentation as data collection techniques. The study results indicate that customer default is characterized by late payments caused by a decline in income and negligence, which disrupts cash flow and increases financing risks. PT BPRS Taman Indah Darussalam implements resolution through a phased approach, starting from consultation, formal notice, imposition of penalties, to restructuring. Under Islamic law, default in a murabahah agreement is considered a breach of trust that must be resolved fairly. In contrast, under civil law, negligent customers may be subject to penalties such as compensation or enforcement of collateral. Implementing murabahah agreements generally aligns with Sharia principles, but further strengthening is needed in customer selection and risk management. It is recommended that banks tighten their initial assessment processes, enhance Islamic financial literacy for customers, and strengthen monitoring systems and educational approaches to reduce the default rate.